The role of Th17 cells in inflammatory bowel disease and the research progress - Chen, Lu; Ruan, Guangcong; Cheng, Yi; Yi, Ailin; Chen, Dongfeng; Wei, Yanling (Frontiers in Immunology, 2023)
Th17 cells play an important role in the abnormal immune response in inflammatory bowel disease (IBD) and are involved in the development and progression of inflammation and fibrosis. An increasing amount of data has shown that gut microbes are important parts of intestinal immunity and regulators of Th17 cellular immunity. Th17 cell differentiation is regulated by intestinal bacteria and cytokines, and Th17 cells regulate the intestinal mucosal immune microenvironment by secreting cytokines, such as IL-17, IL-21, and IL-26. Solid evidence showed that, regarding the treatment of IBD by targeting Th17 cells, the therapeutic effect of different biological agents varies greatly. Fecal bacteria transplantation (FMT) in the treatment of IBD has been a popular research topic in recent years and is safe and effective with few side effects. To further understand the role of Th17 cells in the progression of IBD and associated therapeutic prospects, this review will discuss the progress of related research on Th17 cells in IBD by focusing on the interaction and immune regulation between Th17 cells and gut microbiota.